Evaluation of Combining Land and Waters Data on Local Gravimetric Geoid Modelling (Case Study : D.I. Yogyakarta Coastal Area) - Wiranata, Halim (2016)
Geoid is the equipotential gravity field of the earth which coincides with the undisturbed-mean sea level. Geoid used as a reference to determining height for scientific and also practical application in a region/nation. Until present, the national Indonesian geoid has not determined accurately yet, especially due to limitation of availability and various level of accuracies gravity data. Local geoid becomes one of solution to produce accurate height reference. For the case of Indonesia as archipelagic country, where the land and water always side by side, a combination of land and water area becomes a necessity. Therefore, this research aims to evaluate the effect of combination of land and water data on local geoid modelling with case study in D.I. Yogyakarta, which has been selected based on its location in the coastal region and its availability of gravity data. The local gravimetric of D.I. Yogyakarta is done by 2D-FFT technique, by combining the data of land and waters gravity data, the height data, the water’s depth and also EGM 2008 data. The local gravimetric geoid in coastal area is controlled by 4 control points. Geometric undulations in 4 control points obtained from co-sited GNSS/water pass leveling measurement. The results show that the combination of land and waters data in the computation of local gravimetric geoid increased the mean accuracy of 4 control points becomes 0.0813 m. In addition, the waters data give the positive contribution to local geoid model of D.I. Yogyakarta and also make it more representative and real than before.